US — CHINA — RUSSIA RELATIONS: SPHERES OF INTERDEPENDENCE AND RUSSIA’S PRIORITIES - S. M. Troush (Сравнительная политика)
Russia and China have obvious differences in their approach to the role of the US in the emerging world order. This differences stem from the unique geoeconomic characteristics of the two countries, their motivations for growth, composition and level of their industries, scale of presence in the global trade and financial markets. Some of these differences put Russia apart from the other members of BRICS.